How mentoring and training helps young agripreneurs move their ideas into bsuinesses - Nsanganira, Tony R. (Technical Centre for Agricultural and Rural Cooperation, 2018)
Tony Nsanganira, Youth Employment in Agribusiness Specialist at FAO, shares his experience on mentoring and training of agricultural entrepreneurs in bringing their idea into a business.